Characterization of Myofibrillar Protein from Goldband Goat Fish (Upeneus moluccensis) and Bigeye Scad Fish (Selar crumenophthalmus) - Achmad Subagio; Wiwik Siti Windrati; Mukhammad Fauzi; Yuli Witono (Jurnal Teknologi dan Industri Pangan, 2004)
Characteristics of myofibrillar protein from goldband goat fish (U. moluccensis) and bigeye scad fish (S. crumenophthalmus) were studied for their development as food ingredient. Color analysis using chromameter showed that myfibrillar protein from goldband goat fish was light colored, while that of bigeye scad was slightly drak colored. Proximate analysis showed that their contents were similar by crude protein 7-10%, crude fat 0.2-0.5%, and ash 0.4-0.7%. Amino acid compositions of both myofibrillar proteins were very close, dominated by glutamic acid (20%), aspartic acid (10%) and lysine (9%). However, comparing with bigeye scad, myofibrillar proteins from goldband goatfish were easily aggregated, had higher gelation capacity and higher emulsion activity, but lower solubility. Based on these result, myofibrillar protein from goldband goatfish has good charachteristics as food ingredient especially for restructured products comparing with bigeye scad. Key words : Myfibrillar, goldband, goat fish, bigeye scad fish, proteins.